Highly efficient perovskite solar cells incorporating NiO nanotubes: increased grain size and enhanced charge extraction. Issue 41 (4th October 2017) - Yun, Juyoung; Jun, Jaemoon; Yu, Haejun; Lee, Kisu; Ryu, Jaehoon; Lee, Jungsup; Jang, Jyongsik
Abstract : Incorporating NiO NTs in perovskite films provided an enhanced grain size and charge extraction, resulting in an improved PCE of 19.3%. Abstract : Perovskite solar cells (PSCs) have greatly improved through optimizing the morphology and charge extraction of the perovskite film. To increase the efficiency, we have developed a new method of adding NiO nanotubes (NTs) to the perovskite precursor solution. The NiO NTs promoted the growth of perovskite grains during annealing and facilitated charge extraction. The increase in the grain size improved the crystallinity of the perovskite film and reduced the grain boundaries that could trap charge. Additionally, the NiO NTs located between the grain boundaries transferred holes, which prevented charge recombination. The efficiency of the PSCs increased due to the improved crystallinity and charge extraction of the perovskite film. Devices incorporating the NiO NTs exhibited power conversion efficiencies of 19.3 and 12.82% for planar-type and carbon-based PSCs, respectively.